Neuropharmacological effects of the petroleum ether/ethyl acetate stem bark extract of Maerua Angolensis D.C (Capparaceae) - Benneh, Charles Kwaku (2016)
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Philosophy in the Department of Pharmacology,